PTH-077 Vedolizumab in the real world: a tertiary centre experience. (17th June 2017) - Manning, C; Chan, S; Tremelling, M; Tighe, R
Abstract : Introduction: Vedolizumab is a gut selective α4β7 integrin antibody licenced for treatment of moderate to severe inflammatory bowel disease (IBD) in patients not responding or intolerant to immunomodulators or TNF-alpha antagonists. It has been shown to be effective at induction and maintenance of remission, with a good safety profile [1] . As it is increasingly used in clinical practice we wanted to confirm its effectiveness and safety in our cohort of patients. Method: IBD patients receiving Vedolizumab at Norfolk & Norwich University Hospital from March 2015 to January 2017 were identified. Details of IBD diagnosis, previous treatments, therapy duration, clinical response and remission were obtained by case notes review. Results: 53 IBD patients (26 male, 27 female) were identified; 27 with Crohn's, 26 with ulcerative colitis (UC). 18 have since stopped Vedolizumab, while 35 continue. 16 patients received a concomitant immunomodulator. 9 patients were anti-TNF naïve, 44 previously failed anti-TNF therapy. 41 patients (77%) showed initial response to treatment (20 Crohn's, 21 UC). 7 patients (13%) were primary non-responders and stopped therapy. 2 patients stopped therapy within 1 month due to side effects. 3 patients have been treated for less than 2 months and it is too early to assess response. Of the 41 initial responders, 5 subsequently stopped due to loss of response, and 1 had to stop due to side effects. A further 3 received treatment during a clinical trial and stopped therapy when funding was withdrawn despite maintained remission. 32 patients remain in clinical response on Vedolizumab since initiation (60%). 12 of these patients are in clinical remission. 3 additional patients are on treatment but yet to show response, pending further assessment. Longest treatment period is currently 20 months, with mean duration of 7 months. While response rates are broadly similar between UC and CD, 21 (81%) and 20 (74%) respectively, in this panel Crohn's patients have a higher remission rate; with 10 patients currently maintaining remission (36%) compared to 2 UC patients (8%). This is probably related to treatment duration (mean duration of 10 months in Crohn's compared to 5 months for UC). Vedolizumab has been well tolerated in our cohort, with only 3 patients (6%) developing side effects (listeria infection, perianal sepsis, and chronic cough). Conclusion: These results confirm that Vedolizumab is a safe and effective treatment for IBD patients intolerant of or unresponsive to immunomodulators/anti-TNF therapy, or where these are contra-indicated. A majority of our patients have shown response to treatment and 12 (23%) achieved sustained remission with a very low incidence of side effects. Reference: . Sandborn WJet al. Vedolizumab as induction and maintenance therapy for Crohn's disease. N Engl J Med 2013;369:711–721. Disclosure of Interest: None Declared